Lemea, The Rejang Tribe'S Traditional Food Made From Fermented Bamboo Shoots (Review) - Rozi Satria Utama; Prima Yaumil Fajri; Agustina Agustina; Jerry Antonio (UNIVED Press, Dehasen University Bengkulu, 2023)
Lemea is a traditional food made from fermented chopped bamboo shoots and fish. It is a traditional food of the Rejang tribe in Bengkulu, Sumatera. Lemea is not eaten raw due to its strong flavor and aroma, but rather cooked with simple spices and served with fish or shrimp. It is commonly cooked in a spicy sambal lemea and served as a dish with rice. This review aims to spread information about lemea and its various studies. Several researchers have altered the lemea production process to improve product quality, such as blanching raw materials, fish raw materials, and fermentation containers. The fermentation of lemea is spontaneous fermentation. Lactobacillus plantarum C410L1 and Lactobacillus rossiae LS6 have been identified as lactic acid bacteria from lemea. These bacterial isolates have potential as probiotics because of their good resistance to pH, temperature, and salt concentration.